MIGRATION AND MISSION: THE PLANTING OF FRAFRA CHURCHES IN ASHANTI - Adubufour, Samuel B. (Ghana journal of religion and theology, 2017)
The advent of mono-ethnic churches in Southern Ghana for migrants from the North is a new development in Ghanaian Christianity. The new churches were generated by the prominent presence of migrants from Northern Ghana to the southern parts of the country. Church surveys undertaken by the Ghana Evangelism Committee revealed the mission opportunities that the phenomenon of migration from the north presented the churches in the south. The Frafra Churches have been selected for study because of their predominance in the mono-ethnic category of churches in the Ashanti region. The study establishes that the Frafra Christian Fellowship played a principal role in the planting of Frafra churches. Furthermore, the study highlights the cardinal importance of the mother-tongue in indigenous mission work. Other critical missiological issues raised for further consideration are the bane and blessing of migration, the significance of worldview in urban missions, linguistic factors in indigenizing mission and discipleship, and the imperative of a sense of community in urban churches.